Peran Aktif Masyarakat Terhadap Koperasi Syariah Di Kabupaten Pringsewu - Fadhillah, Ahmad; Sunarko, Adang; Oktavia, Rahmah (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2023)
Sharia cooperatives are a type of cooperative whose goals, principles and business activities are based on sharia principles. This principle refers to Islamic law which is based on fatwas issued by the National Sharia Council of the Indonesian Ulema Council. This research aims to determine the role of the community in improving sharia cooperatives in Pringsewu Regency. The study was conducted using a qualitative research study. The impact of sharia cooperatives can encourage people, especially business people, to achieve and develop the businesses they start. Sharia cooperatives focus on principles that do not involve the practices of usury, gharar and maysir. Through this approach, sharia cooperatives help keep us away from actions that are forbidden by Allah. One practice that must be avoided in sharia cooperatives is applying for capital loans to loan sharks.